Structure and properties of nano-confined poly(3-hexylthiophene) in nano-array/polymer hybrid ordered-bulk heterojunction solar cells - Foong, Thelese Ru Bao (2013)
The ordered-bulk heterojunction (BHJ) photovoltaic device comprising a semiconducting donor polymer incorporated into pristine/unmodified vertically aligned arrays of metal oxide acceptor nanotubes/nanorods is widely perceived as being structurally ideal for energy conversion but the power conversion efficiencies of such devices remain relatively low (in the order of η = 0.6%) when compared with bilayer or non-ordered bulk heterojunction systems. We explain the incongruity by investigating the morphology and microstructure of regio-regular poly(3-hexyl thiophene) (P3HT) infiltrated and confined within the cavities of TiO2 nanotube arrays. A series of TiO2 nanotube arrays with different nanotube diameters and inter-nanotube spacings are fabricated by the liquid-phase atomic layer deposition (LALD) technique, and P3HT is infiltrated into the array cavities via a vacuum-annealing technique. X-Ray diffraction studies reveal that the P3HT chains in both nano-confined and non-confined (i.e. planar film) environments are well-aligned and oriented edge-on with respect to the underlying substrate. Up to 2.5-fold improvement in the incident-photon-to-converted-electron efficiency (IPCE) is observed in ordered-BHJ structures over benchmark planar devices which we attribute to the increase in interfacial area resulting from the use of the nanostructures. However, the large effective surface area conferred by the nano-arrays (up to 9.5 times that of the planar system) suggests that much higher efficiencies could be harnessed. Our study shows that the morphology and orientation of the infiltrated polymer play a critical role in the charge transport of the device, and suggests that better understanding and control of polymer morphology under nano-confinement in the nano-array will be the key to fully reaping the promised benefit of ordered-BHJ devices.